PERAN WIRAUSAHA BERJAMAAH DAN INDIVIDU BERKARAKTER DALAM PENGUATAN INDUSTRI HALAL DI INDONESIA - Dhoya Safira Tresna Lestari; Muhammad Hamdan Ainulyaqin; Sarwo Edy (Jurnal Ilmiah Ekonomi Islam, 2023)
This research is motivated by the growth of the halal industry which is increasing every year. This study discusses the presence of innovation in entrepreneurial activities in general, namely congregational entrepreneurship. The presence of a congregational entrepreneurial community run by individuals with character is expected to be able to provide new breakthroughs for existing business structures in Indonesia. The author uses library research methods and field research in conducting this research. The results of this study explain that the presence of a congregated entrepreneurial community has quite an influential impact on the Indonesian economy, especially in strengthening the halal industrial sector, because one of the goals of forming an entrepreneurial community is to increase the number of entrepreneurs in Indonesia. The presence of the congregational entrepreneurial community also makes it a means for entrepreneurs and prospective entrepreneurs to get convenience in running their business, both in terms of knowledge, experience and materials.